(untitled) (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2021)
In the U.S., majority of public schools follow scripted curriculum and teacher-directed teaching. Although Project Based Learning is apparent in a few schools throughout the U.S, most schools, specifically lower income and urban schools do not have Project Based Learning in their science classrooms. Therefore, students may not have the ability to explore learning content through hands-on experiences and through relatable interest. Yet, according to research, Project Based Learning can improve the skills and learning of students in the classroom and increase test scores. Thus, based on research, this manuscript will discuss information on Project Based Learning and support the claim that Project Based Learning should become the main pedagogy in science classes in K-12 public schools.